Evaluation of an intervention to increase topical sunscreen use in German outdoor workers: study protocol for the non-randomised controlled intervention study ProtExSun - Dick, Anja; Rocholl, Marc; Ludewig, Michaela; Skudlik, Christoph; Jakaša, Ivone; Kezic, Sanja; de Boer, Florentine; van der Molen, Henk F; John, Swen Malte (BMJ open, 2025)
IntroductionSquamous cell carcinoma and multiple actinic keratoses caused by solar ultraviolet radiation (UVR) are among the most frequently recognised occupational diseases in Germany. Employees who regularly work outdoors, for example, in the construction industry, agriculture, forestry and gardening, are at a higher risk of developing occupational skin cancer. However, sun-safety behaviour in outdoor workers is currently insufficient. Therefore, this study aims to investigate the effectiveness of an intervention to increase sunscreen use among outdoor workers.Methods and analysisIn this non-randomised, controlled intervention study, 234 outdoor workers from different companies in industries with outdoor working activities based in Germany will be included. The study population, aged 18 years and above, has to be intensively exposed to solar UVR of regularly 1 hour or more per day. The intervention group will receive a sunscreen package as well as health education. The control group follows the practice in their companies (‘treatment-as-usual’). At the beginning of the study, after 3 months and at the end of the study (after 6 months), both groups filled in different questionnaires. In addition, stratum corneum (SC) samples will be collected at the beginning and after 3 months. The primary outcome—increase in the frequency of sunscreen use during work and in leisure time—will be assessed from data on self-reported sunscreen use. The secondary outcomes include sun protection behaviour, knowledge about sun protection and skin cancer, and acceptance of the provided sunscreens. Further secondary outcomes include internal UV dose and UV-related immune response, determined by the levels of SC biomarkers. Data will be analysed using both descriptive and inferential methods.Ethics and disseminationThe study protocol followed the principles of the Declaration of Helsinki (2013) and was approved by the Ethics Committee of Osnabrück University, Germany (reference Ethik-37/2024). Study results will be disseminated through peer-reviewed publications and conference presentations.Trial registration numberDRKS00035178.